The Analysis Study of Effectiveness of Vitamin D Supplementation for Prevention of Open Angle Glaucoma: A Comprehensive Systematic Review - Cintya Ristimawarni; Kaharuddin; Nazza Rizky Ramdhagama (International Medical Journal Corp. Ltd, 2025)
Background: Over 70 million people worldwide suffer from glaucoma. Over the next 20 years, this is anticipated to rise to 111 million. Primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG) are the two principal subtypes of glaucoma. The most prevalent glaucoma subtype is POAG. The aim: The aim of this study to show about effectiveness of vitamin D supplementation for prevention of open angle glaucoma. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Seven publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Despite being mostly unknown, the relationship between vitamin D and POAG is particularly intriguing because, when taken as directed, vitamin D is a reasonably priced and safe supplement. It seems that vitamin D protects against oxidative damage and the generation of reactive oxygen species (ROS). Consequently, hypotheses linking vitamin D to POAG include the vitamin's antioxidant properties and its function in inhibiting inflammatory gene expression.